Influenza Vaccination among Pregnant Women: Patient Beliefs and Medical Provider Practices - Stark, Lauren M. (Infect Dis Obstet Gynecol, 2016)
ACOG's research department recruited four medical centers to participate in a study on the attitudes and practices of medical providers and pregnant patients regarding influenza vaccination. Medical providers and patients were given voluntary surveys and medical record data was collected over two flu seasons, from 2013 to 2015. Discrepancies between self-reports of medical providers and patients and medical records were observed. Nearly 80% of patients self-reported accepting the influenza vaccine, but medical record data only reported 36% of patients accepting the vaccine. Similarly, all medical providers reported giving recommendations for the vaccine, but only 85% of patients reported receiving a recommendation. Age, education, a medical provider's recommendation, and educational materials were found to positively influence patient beliefs about the influenza vaccine. Accepting the vaccine was influenced by a patient's previous actions, beliefs, and a medical provider's recommendation. Patients who reported previously not accepting the vaccine and had negative feelings towards the vaccine but accepted it while pregnant reported concern for the health and safety of their baby. Future research should focus on groups that may be less likely to accept the vaccine and ways to dispel negative myths. Medical provider should continue to strongly recommend the vaccine and provide educational materials.